Właściwości negocjacji w Unii Europejskiej: wybrane aspekty teoretyczne - Cyryło, Barbara (Rocznik Integracji Europejskiej, 2015)
The focus of the paper is the selected, most significant theoretical aspects of negotiations conducted within the European Union. They include the following: the large number and diversity of negotiators; the specific subject of EU negotiations, making them multi-level and multi-dimensional; the multistage character of EU negotiations and, thus, the involvement of various actors at different levels, calling for different kinds of negotiating activities; and, last but not least, the top-down and bottom-up processes that are the determiners of negotiations in the EU.